Putusan Pemidanaan dalam Perkara Tindak Pidana Membantu Menyediakan Pornografi Anak: Studi Putusan PN Bandung - Lely Lestari; Endah Dwi Nurhayati; Fiska Maulidian Nugroho; Y.A. Triana Ohoiwutun (Rechtenstudent, 2023)
Pornography is an act that causes anxiety and concern for the community. Viewing pornographic videos is increasingly accessible, both through print and electronic media. The development of media with pornographic elements has increased the existence of pornographic crimes among the public. The definition of a pornographic crime is an immoral act related to sex in the form of a picture, sketch, photograph, writing, video or through other media shown in public which violates the norms of decency in society. This study aims to, firstly, analyze the suitability of the Bandung District Court's decision number 517/Pid.Sus/2018/Pn.Bdg regarding the crime of assisting in providing child pornography based on trial facts. Second, analyzing the imposition of weighting for criminal law subjects that are specific in nature. This research method uses normative juridical research methods with statutory and conceptual approaches. The conclusions obtained are, firstly the Judge in his ruling stated that the defendants were proven guilty of committing the crime of helping to provide child pornography which was not in accordance with the facts of the trial as seen from the testimony of witnesses and the testimony of the defendant and in that decision the victim was a child so the actions of the defendants were more in line with the crime allowing children to commit obscene acts, therefore the punishment is heavier than the Pornography Law. Second, the Pornography Law does not regulate the burden of criminal penalties for special criminal law subjects such as those closest to the victim. When compared with the Child Protection Act, this regulates criminal sanctions for legal subjects of special criminal offenses with an additional 1/3 (one third) of the threat of the article. So the punishment for those closest to the child is more severe than for other people who are not the closest person to the child victim.